Worse and Worse and Worse: Essential Tremor Patients’ Longitudinal Perspectives on Their Condition - Gutierrez, Jesús; Park, Jemin; Badejo, Olufunmilayo; Louis, Elan D. (Frontiers in Neurology, 2016)
Background: Essential tremor (ET) patients regularly inquire about their prognosis. Therefore, physicians have cause to review available medical literature for meaningful answers. Longitudinal studies are ideally suited to provide a glimpse into the evolution of tremor. Despite its high prevalence, there are surprisingly few longitudinal clinical studies of ET. Furthermore, none of them provided data from the patients’ perspective. Understanding the patient vantage point is valuable as it is the starting point of personalized medicine. Given the progressive nature of ET, we hypothesized that many patients will experience an increase in symptom severity over time. However, due to a lack of clinical data, the exact nature of this progression is unclear. For example, whether patients experience a worsening at each time interval is simply not known. In this longitudinal study, we assessed whether ET patients felt that their symptoms had worsened between each follow-up evaluation and try to identify specific clinical characteristics associated with this experience. Methods: A cohort of 164 ET cases enrolled in a prospective, longitudinal research study. After a baseline in-person assessment, they received regular telephone evaluations for up to 5.25 years, beginning in 2009. During each follow-up evaluation, cases answered the question, “has your ET worsened since our last call?” Results: Two-thirds (104 [63.4%]) of ET cases reported worsening at one-half or more of their follow-up evaluations. Furthermore, one-in-four cases (44 [26.8%]) reported worsening at every follow-up evaluation. Self-reported worsening was not associated with any of the baseline clinical variables assessed, including age, gender, tremor duration, age at tremor onset, or total tremor score. Conclusions: Little has been written from the patient perspective on progression of ET. When followed longitudinally at regular intervals, a majority of ET cases we studied reported worsening one-half or more of the time; furthermore, one-in-four reported worsening at each and every assessment, indicating that they felt they were inexorably getting worse and worse with time. That there is so much self-reported worsening in ET argues against the notion that this is a static and benign condition. It suggests that patients experience it as a condition that worsens regularly and consistently.